2009
DOI: 10.1111/j.1365-2648.2009.04994.x
|View full text |Cite
|
Sign up to set email alerts
|

Silence, power and communication in the operating room

Abstract: Title. Silence, power and communication in the operating roomAimThis paper is a report of a study conducted to explore whether a 1- to 3-minute preoperative interprofessional team briefing with a structured checklist was an effective way to support communication in the operating room.BackgroundPrevious research suggests that nurses often feel constrained in their ability to communicate with physicians. Previous research on silence and power suggests that silence is not only a reflection of powerlessness or pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 29 publications
6
88
0
2
Order By: Relevance
“…The theatre nurses may be reluctant to speak up about safety concerns and patient safety may be negatively affected (1). The hierarchy threatened safety because less powerful members had limited input in decision making, and were reluctant to speak up (15,33,39). In our study the theatre nurses feel they lose their concentration and focus when communication is not respectful in the team.…”
Section: Respectingmentioning
confidence: 79%
“…The theatre nurses may be reluctant to speak up about safety concerns and patient safety may be negatively affected (1). The hierarchy threatened safety because less powerful members had limited input in decision making, and were reluctant to speak up (15,33,39). In our study the theatre nurses feel they lose their concentration and focus when communication is not respectful in the team.…”
Section: Respectingmentioning
confidence: 79%
“…This may be related to physicians' tendencies to de-emphasize relational aspects of patient care in favour of 'case knowledge' which emphasizes medical diagnostic and treatment-of-disease approaches (SteinParbury & Liaschenko, 2007). In the operating room, observational research showed how nurses use a variety of communication strategies, including not communicating at all, to negotiate constraints on their role autonomy in relation to physicians' (Gardezi et al, 2009). Observations of nurses' disengagement from collaborative practice have found that physicians neglect to incorporate the core values of nursing practice into interprofessional care, thus impacting nurses' willingness to collaborate (Miller et al, 2008).…”
Section: Implications For Interprofessional Practicementioning
confidence: 99%
“…Moreover, surgical nurses have intense emotional demands, including feeling responsible for keeping peace during surgery by 'knowing the surgeon's soul' (Riley & Manias, 2006, p. 1548. They find it difficult to speak up when procedures (might) go wrong (Gardezi et al, 2009) and they experience inner conflicts about how to react adequately to 'emotional abuse' including being 'belittled, ridiculed, yelled and sworn at' (Higgins & MacIntosh, 2010, p. 322). Feeling responsible for keeping peace and experiencing verbal insults is stressful and can lead to cognitive stress symptoms such as impaired allocation of attention to the task (Pereira, Müller, & Elfering, 2015).…”
Section: Introductionmentioning
confidence: 97%